Blueprint : SaniSmart / Adlina Anati Abdul Aziz, Ain Nazira Mohd Tahir and Lyana Ibrahim - Abdul Aziz, Adlina Anati; Mohd Tahir, Ain Nazira; Ibrahim, Lyana (2021)
Due to the Covid-19 pandemic started in late 2019, hygiene has become the most important aspect in life and many people have been more critical when it comes to cleanliness and protecting themselves from the coronavirus. Number of cases and deaths in many countries continue to surge. Good hygiene practice is extremely crucial in today’s condition. However, it may not be as easy and practical for many people. Applying hand sanitizer might seem like an easy task, but the traditional way of pouring out of the bottle can be a nuisance. Some companies have come up with a solution, a hand sanitizer bracelet to further assist people in applying hand sanitizer, however there are some flaws to it. Therefore, ALN Sn. Bhd. has come up with a better, upgraded version of it, SaniSmart. It is equipped with refillable and rechargeable features, easy dispenser and reminder system. SaniSmart is created to enhance and innovate existing products, with the consumers' needs in mind. The target market for this new product development are healthcare services staff, delivery services workers, as well as full and part time workers where their jobs require them to be outside and meeting people, which could make them more at risk of being infected by Covid- 19. It is a part of business to have competitors, and ALN Sdn. Bhd. has a few major ones. They are Jin Sheu Enterprise, Wristband Enterprise and Pyoor Enterprise. Nevertheless, ALN’s product certainly has an edge over the other competitors' products in terms of better technology, functionality and aesthetic values while still maintaining a reasonable price tag.